FUS-mediated blood-brain barrier disruption for delivering anti-Aβ antibodies in 5XFAD Alzheimer's disease mice - Antoniou, Anastasia; Stavrou, Marios; Evripidou, Nikolas; Georgiou, Elena; Kousiappa, Ioanna; Koupparis, Andreas; Papacostas, Savvas S.; Kleopa, Kleopas A.; Damianou, Christakis A. (My University, 2023)
Amyloid-β (Aβ) peptides, the main component of amyloid plaques found in the Alzheimer's disease (AD) brain, are implicated in its pathogenesis, and are considered a key target in AD therapeutics. We herein propose a reliable strategy for non-invasively delivering a specific anti-Aβ antibody in a mouse model of AD by microbubbles-enhanced Focused Ultrasound (FUS)-mediated Blood-brain barrier disruption (BBBD), using a simple single stage MR-compatible positioning device.
Keywords: Alzheimer’s disease; Anti-Αβ; Antibody; BBB; Mice; Ultrasound